Pengaruh Budaya Organisasi, Gaya Kepemimpinan, dan Pelatihan Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Sebagai Pemoderasi - Chaterine Gouwtama; Toni Yoyo (Komunitas Dosen Indonesia, 2025)
This study investigates the impact of organizational culture, leadership style, and training on employee performance, with job satisfaction acting as a moderating variable. Utilizing the Structural Equation Modeling (SEM) approach and Smart PLS software, the study analyzes the relationships between variables. A saturated sampling method was employed, involving all 157 employees of Buddhi College School as respondents. The findings confirm the proposed hypothesis, indicating that organizational culture, leadership style, training, and job satisfaction positively and significantly influence employee performance. However, job satisfaction moderates the relationship between organizational culture and employee performance negatively and significantly. Conversely, job satisfaction positively and significantly moderates the effects of leadership style and training on employee performance. These findings suggest that organizations aiming to enhance employee performance should focus on strengthening organizational culture, leadership effectiveness, training programs, and job satisfaction.